Acidic compost tea enhances phosphorus availability and cotton yield in calcareous soils by decreasing soil pH. (17th November 2021) - Luo, Tong; Zhu, Yuanji; Lu, Weidan; Chen, Lili; Min, Tao; Li, Junhua; Wei, Changzhou
ABSTRACT: The long-term application of chemical fertilisers in calcareous soil causes the stable P in soil to accumulate and not be effectively utilised. In this study, whether acidic compost tea (CT) could increase the available P in calcareous soil was evaluated through a pot experiment. The P forms of the samples were analysed using Hedley sequential P fractionation. CT had significant effects on different soil P fractions and P uptake ( p  < 0.05). Compared with organic fertiliser (OF), acidic CT increased the availability of H2 O-P and NaHCO3 -P by 15.9% and 12.6%, respectively, it mainly comes from the dissolution of HCl-P and residue-P. CT also promoted the growth and yield of cotton and significantly increased P use efficiency by 13.8% and 31.6% ( p  < 0.05), respectively, compared with OF, because the H + in CT reduced the pH of the calcareous soil, promoted the dissolution of stable P in soil, and reduced the fixation of P from the fertiliser. However, the organic matter in CT did not contribute much to the desorption of P. These findings provide a new idea for the activation and utilisation of P in calcareous soil.